MarketBusters : 40 strategic moves that drive exceptional business growth - McGrath, Rita Gunther; MacMillan, Ian C., 1940- (Boston : Harvard Business School Press, 2005)
"In this hands-on guide, Rita Gunther McGrath and Ian C. MacMillan identify powerful strategic moves they call "MarketBusters" - approaches that dramatically reconfigure profit streams in an industry, upend conventional competition, and ultimately deliver blockbuster growth." "Based on insights from an extensive three-year study, McGrath and MacMillan describe forty proven marketbusting moves and outline five overall strategies companies have used to drive new growth."--BOOK JACKET.
MarketBusting strategies -- Transform the customers' experience -- Transform your offerings and their attributes -- Redefine your profit drivers -- Exploit industry shifts -- Exploit emerging opportunities -- Executing marketBusting strategies -- MarketBuster case study : Royal Insurance Italy.
Includes bibliographical references (pages 237-244) and index.
Description based on print version record.
Keywords: Strategic planning -- Handbooks, manuals, etc; Customer relations -- Management -- Handbooks, manuals, etc; Strategische planning; Klantgerichtheid; Strategic planning -- Handbooks, manuals, etc; Customer relations -- Management -- Handbooks, manuals, etc; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books